The Implementation of the Spirit of National Defense and Students Caring Attitude Through Extracurricular Scouting Activities - S. Saripuddin; Muhammad Fahreza W; R. Rahmawati; N. Nurdin (Golden Ratio of Data in Summary, 2024)
The objectives of this research include: 1) To find out the general description of the implementation of the spirit of state defense of students at SMK Negeri 1 Pangkep. 2) To find out the general description of the caring attitude of students at SMK Negeri 1 Pangkep. 3) To find out and analyze the implementation of the spirit of state defense and the caring attitude of students through extracurricular scouting activities at SMK Negeri 1 Pangkep. The type of research chosen is qualitative narrative using the case study method. This research was conducted at SMK Negeri 1 Pangkep, South Sulawesi Province. in the third week of May 2024 to the fourth week of July 2024. Data collection techniques in this study through observation, interviews and documentation. The results showed that the implementation of the spirit of state defense with its indicators was well implemented, namely (1) love of the homeland, (2) Awareness of the Nation and State, (3) Belief in the State Ideology Pancasila, (4) Willing to Sacrifice for the Nation and State, not yet optimal (5) Have the Ability to Defend the Country. Then the implementation of the social care attitude of students at SMK Negeri 1 Pangkep is included in the category that has been well implemented through indicators: (1) honesty, (2) compassion, (3) humility, (4) friendliness, (5) kindness, and (6) always helping others. And in general, the relationship between the spirit of state defense, caring attitudes and extracurricular activities of students at SMKN 1 Pangkep through indicators, namely (1) discipline, (2) independence is still not optimal, (3) having noble character and noble character, (4) having the spirit of Pancasila, being loyal and obedient to the Republic of Indonesia, still needs to be improved (5) attitude of togetherness, (6) paying attention to common interests, (7) polite behavior, (8) respect for others, (9) cooperation attitude, and (10) sense of belonging.